ISOLASI BAKTERI PENGHASIL ENZIM PROTEASE BACILLUS THURINGIENSIS IRODI PADA ONCOM MERAH PASCA FERMENTASI 24 JAM - Radna Safitri; Sakti Imam Muchlissin; Ana Hidayati Mukaromah; Sri Darmawati; Stalis Norma Ethica (Universitas Muhammadiyah Semarang, 2018)
The need for protease enzymes in Indonesia and the world continues to increase, requiring new protease sources. Bacteria are beneficial sources of protease because they are easy to obtain and rapidly multiply. Bacterial identification could be done molecularly through analysis of the 16S rRNA gene. This study aimed to obtain an isolate of protease-producing bacterium from 24-h post-fermented red oncom and to identify the obtained bacterial strain molecularly by 16S rRNA gene sequence. The protease production test on bacteria found in red oncom sample was done using a selective medium, Skim Milk Agar (SMA). DNA genomes of proteolytic bacterial cells were extracted by Promega KIT. The amplifying process of 16S rRNA gene using the Polymerase Chain Reaction (PCR) method. The amplified DNA were analyzed using the BLAST program. The results of the research found 8 isolate of bacterias. The most unique isolate was IROD1.3. It has significant proteolytic activity based on the ability to produce clear zone of protease on SMA medium with a diameter of 85,00 mm. Isolate IROD1.3 was identified molecularly as Bacillus thuringiensis with similarity of 96% to the sequence of 16S rRNA gene Bacillus thuringiensis strain TERI SID4 (Genbank access code: KX822158.1). Keywords: Protease, 16S ribosomal RNA gene, red oncom, proteolytic bacterium